A novel necroptosis-related lncRNA signature predicts the prognosis and immune microenvironment of hepatocellular carcinoma - Wang, Jianguo; Shen, Bingbing; Liu, Xinyuan; Jiang, Jianxin (Frontiers in Genetics, 2022)
Hepatocellular carcinoma (HCC) is one of the malignant tumors with the highest mortality and the worst prognosis in the world. Necroptosis is a programmed death mediated by RIP1, RIP3, and MLKL. The aim of this study was to create a new Necroptosis-related lncRNAs (NRlncRNAs) risk model that can predict survival and tumor immunity in HCC patients. The RNA-seq data and clinical data were obtained from The Cancer Genome Atlas (TCGA) database. NRlncRNAs were identified by Pearson correlation analysis. The LASSO-Cox regression analysis was used to build the model, and it was evaluated using the ROC curve and the area under the Kaplan-Meier curve. In addition, clinicopathological correlation analysis, differential expression analysis, PCA, TMB, GSEA enrichment analysis, immunocorrelation analysis, clinical therapeutic compound prediction, and QRT-PCR were also performed. We built a model including six necroptosis-related lncRNAs. The calibration plots in the model displayed superior agreement with the prognosis prediction. The model's one-, three-, and five-year OS under the ROC curve (AUC) values were 0.746, 0.712, and 0.670, respectively. Furthermore, we discovered significant differences in functional signaling pathways, immunological state, mutation profiles, and medication sensitivity between high-risk and low-risk patient groups. QRT-PCR confirmed the high expression of 3 NRlncRNAs in HCC cells. Overall, NRlncRNAs play a significant role in HCC, and these six NRlncRNAs can predict HCC patient prognosis. They could be important in the future for personalized cancer treatments.